Puzzle-based learning media design for early childhood spice introduction to support cultural education - Andin Rahmani; Nurul Fitriana Bahri (Pascasarjana Institut Seni Indonesia Surakarta, 2026)
This study aims to design a puzzle-based educational toy for introducing Indonesian spices to early childhood learners as an effort to support cultural education and preserve local knowledge. The study was conducted at Cihaurgeulis Early Childhood Education Center, Bandung, involving children aged 4–6 years and four teachers. A Qualitative and Development Research (Q&D) approach was employed using observations, interviews, thematic analysis, and the ADDIE instructional design model up to the development stage. The analysis revealed that children showed strong interest in puzzle-based learning activities, yet their knowledge of Indonesian spices was limited, with most children recognizing only one or two spice types. Based on these findings, a puzzle-based learning medium was designed, consisting of spice-themed puzzle pieces, flashcards, magnetic learning cards, and authentic spice samples integrated into a contextual learning framework. The design was developed according to the cognitive characteristics of children in the intuitive thinking stage, emphasizing concrete, visual, and hands-on learning experiences. Initial prototype trials and teacher evaluations indicated that the learning media were appropriate for classroom implementation and supported children’s engagement in learning activities related to Indonesian spice heritage. The study suggests that culturally integrated puzzle-based learning media can serve as an innovative educational tool for introducing Indonesian spices while supporting contextual and culture-based learning in early childhood education.